Multibeam bathymetry processed data (Kongsberg EM122 working area dataset) of RV SONNE during cruise SO260/1, Argentine Continental Margin - Fynn Warnke; Tilmann Schwenk; Elda Miramontes; Volkhard Spieß; Stefan Wenau; Graziella Bozzano; Michele Baqués; Sabine Kasten (PANGAEA, 2023)
The data comprise processed bathymetry and backscatter grids from the Ewing Terrace on the Argentine Continental Margin that were acquired during RV SONNE cruise SO260/1 in 2018. Bathymetric and backscatter data acquired using the 12 kHz Kongsberg EM122 echosounder were processed using the Open Source software MB-System. This includes navigation editing, interactive sound velocity corrections, erroneous beam flagging and grid generation. Backscatter grids of the recorded amplitude variations were created after normalizations using an angle varying gain (AVG) correction considering the seafloor morphology.